Wireless light-emitting device for the determination of chirality in real samples. (20th July 2022) - Salinas, Gerardo; Bonetti, Giorgia; Cirilli, Roberto; Benincori, Tiziana; Kuhn, Alexander; Arnaboldi, Serena
Highlights: Bipolar electrochemistry as transduction method for chiral recognition. Enantiomeric excess quantification of amino acids with bipolar chiral electrochemistry. Determination of chirality in real samples through wireless light emission. Abstract: Bipolar electrochemistry can be employed in the context of chiral recognition in order to obtain useful analytical readouts of enantiomeric analytes. Herein, we employ this concept for the simultaneous determination of two enantiomers present in solution, and its possible use as transduction mechanism for complex real matrices analysis. This approach is based on the combination of the enantioselective electrooxidation of only one of the two antipodes of a chiral analyte with the emission of light from light-emitting diodes (LEDs). A double hybrid device was designed, using the enantiomers of an inherently chiral oligomer and a bare gold wire as the anode and cathode of a green and red LED. By applying an appropriate voltage, the wirelessly induced redox reactions trigger light emission only when the probe with the right configuration is present in solution. This device was used to simultaneously measure the ratio between L- and D-Tryptophan, both present in solution and to quantify L-ascorbic acid in a commercial juice sample. The measurement correlates with the value reported on the sample specifications. These results illustrate the possible use of such light-emitting bipolar devices as analytical tools for qualitative and quantitative measurements of enantiomeric excess, even in real samples. Graphical abstract: Image, graphical abstract